2013
DOI: 10.1002/lary.23868
|View full text |Cite
|
Sign up to set email alerts
|

Central condylar displacement with brain abscess from chronic mandibular osteomyelitis

Abstract: In this case report, we describe a unique long-term complication from undiagnosed mandibular osteomyelitis. A 53-year-old female who underwent a dental extraction complicated by chronic postoperative odontogenic infection and cutaneous parotid fistula formation 2 years earlier presented with acute mental status change, gradual unilateral facial nerve palsy (House-Brackmann score V), and nontraumatic dislocation of the condylar head into the middle cranial fossa. The patient's chronic mandibular osteomyelitis l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to the authors, the dissemination of the infection was through the blood circulation ( 5 ). Lee T et al ( 6 ) reported a case of central condylar displacement with brain abscess from chronic mandibular osteomyelitis. In this study, the authors hypothesize that the patient’s chronic mandibular osteomyelitis led to glenoid fossa erosion with penetration of the germs in the middle cranial fossa and temporal lobe abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, the dissemination of the infection was through the blood circulation ( 5 ). Lee T et al ( 6 ) reported a case of central condylar displacement with brain abscess from chronic mandibular osteomyelitis. In this study, the authors hypothesize that the patient’s chronic mandibular osteomyelitis led to glenoid fossa erosion with penetration of the germs in the middle cranial fossa and temporal lobe abscess formation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the reported cases were those associated with trauma; however, cases linked to causes other than trauma have recently been reported. These include chronic osteomyelitis [77,109], degenerative changes in the TMJ [107], and asymptomatic intracranial intrusion after orthognathic surgery [108]. A chronic mandibular and/or middle skull base osteomyelitis with a concurrent brain abscess can result in a non-traumatic intracranial condylar head displacement [109].…”
Section: Etiology and Treatment Of Intracranial Dislocation Of The Co...mentioning
confidence: 99%